From screening to intervention: impasses and elucidations granted to nurse navigators in clinical studies - Ferreira, Silvia Kelly Rodrigues; Fernandes, Rhaiane Souza dos Santos Araújo; Siriano, Isabella Rodrigues; Costa, Ana Carolina Barbosa (Mastology, 2026)
Objective: To map the roles of nurse navigators in recruiting patients for clinical trials. Methods: This is an integrative review, based on searches in the Virtual Health Library (VHL), using the terms “nurse navigator”, “clinical research” and “patient recruitment”. The selection included articles published over a 10-year period. Results: In two North American studies, inclusive and didactic approaches were used to clarify the phases of clinical protocols to candidates, resulting in more assertive recruitment with an emphasis on sociocultural heterogeneity. In contrast, a Brazilian study of 173 patients identified difficulties in screening, such as communication problems (24.3%), patient disinterest (16.2%), and missed appointments (16.2%). In addition, another investigation in Brazil revealed that only 1% of health professionals refer cancer patients for clinical trials. However, a survey of 263 patients who were under the care of the nurse navigator found that 97% were satisfied with the service provided, despite the difficulties faced. Conclusion: Faced with these obstacles, it is essential for nurses to identify the patient’s sociocultural obstacles, and to be compatible with previous institutional flows, adapting the model of care provided in the service of origin to the needs of the clinical protocol. Furthermore, it is essential that, as well as sharing the studies with the multi-team, they are fully involved, understanding the criteria and interpreting their scope so that each referral is effective. The nurse navigator, with the support of the Federal Nursing Council, plays a fundamental role in organizational processes in the face of the complexity of health systems. The growing demand for innovation in clinical research requires the recruiter to take an integrated approach, with accessible communication and referrals that facilitate the patient’s journey through the various services available.